Universality classes and critical phenomena in confined liquid systems - Chalyi, A.V.; Bulavin, L.A.; Chekhun, V.F.; Chalyy, K.A.; Chernenko, L.M.; Vasilev, A.M.; Zaitseva, E.V.; Khrapijchyk, G.V.; Siverin, A.V.; Kovalenko, M.V. (Condensed Matter Physics, 2013)
It is well known that the similar universal behavior of infinite-size (bulk) systems of different nature requires the same basic conditions: space dimensionality; number components of order parameter; the type (short- or long-range) of the intermolecular interaction; symmetry of the fluctuation part of thermodynamical potential. Basic conditions of similar universal behavior of confined systems needs the same supplementary conditions such as the number of monolayers for a system confinement; low crossover dimensionality, i.e., geometric form of restricted volume; boundary conditions on limiting surfaces; physical properties under consideration. This review paper is aimed at studying all these conditions of similar universal behavior for diffusion processes in confined liquid systems. Special attention was paid to the effects of spatial dispersion and low crossover dimensionality. This allowed us to receive receiving correct nonzero expressions for the diffusion coefficient at the critical point and to take into account the specific geometric form of the confined liquid volume. The problem of 3D⇔2D dimensional crossover was analyzed. To receive a smooth crossover for critical exponents, the Kawasaki-like approach from the theory of mode coupling in critical dynamics was proposed. This ensured a good agreement between data of computer experiment and theoretical calculations of the size dependence of the critical temperature Tc(H) of water in slitlike pores. The width of the quasi-elastic scattering peak of slow neutrons near the structural phase transition in the aquatic suspensions of plasmatic membranes (mesostructures with the typical thickness up to 10 nm) was studied. It was shown that the width of quasi-elastic peak of neutron scattering decreases due to the process of cell proliferation, i.e., with an increase of the membrane size (including the membrane thickness). Thus, neutron studies could serve as an additional diagnostic test for the process of tumor formation. Подiбнiсть унiверсальної поведiнки систем великих розмiрiв рiзної природи вимагає однаковостi таких основних умов: вимiрностi простору, числа компонент параметра порядку; коротко або далекодiючих мiжмолекулярних взаємодiй; симетрiї флуктуацiйної частини термодинамiчного потенцiалу. Основнi умови подiбностi унiверсальної поведiнки для просторово обмежених систем доповнюються однаковими додатковими умовами: кiлькiстю моношарiв у напрямку просторового обмеження системи; нижньою кросоверною вимiрнiстю, тобто геометричною формою обмеженого об’му; граничними умовами на обмежуючих поверхнях; фiзичними властивостями, якi розглядаються. Метою цiєї оглядової статтi було вивчення умов подiбностi унiверсальної поведiнки процесiв дифузiї у просторово обмежених рiдинних системах. Особливу увагу було придiлено ефектам просторової дисперсiї i нижньої кросоверної вимiрностi. Це дозволило отримати правильнi ненульовi вирази для коефiцiєнта дифузiї у критичнiй точцi з урахуванням конкретної геометричної форми обмеженого об’єму рiдини. При розглядi проблеми 3D ⇔ 2D вимiрного кросовера були отриманi оригiнальнi результати для плавного переходу критичних iндексiв за допомогою пiдходу, схожого на метод Кавасакi в теорiї динамiчного скейлiнгу. Це призвело до гарного узгодження мiж даними комп’ютерного експерименту i теоретичними розрахунками залежностi величини критичної температури Tc(H) води вiд товщини щiлиноподiбних пор. Було дослiджено ширину квазiпружного пiку розсiяння повiльних нейтронiв поблизу структурного фазового переходу в водних суспензiях плазматичних мембран (мезоструктур з типовою товщиною до 10 нм). Доведено, що ширина квазiпружного пiку розсiяння нейтронiв повинна зменшитися внаслiдок процесу клiтинної пролiферацiї, тобто iз збiльшенням розмiру мембрани (у тому числi товщин мембран). Таким чином, нейтроннi дослiдження можуть слугувати додатковим дiагностичним тестом для виявлення процесу утворення пухлини.